PRINSIP-PRINSIP PENGEMBANGAN KURIKULUM - Agnes Nuraeni Muslim; Asep Nursobah; Mohamad Erihadiana (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
The development of science and technology, the implications of which also spread to the world of education, means that education needs to innovate. This also has an impact on curriculum development which needs to adapt to current needs. In its implementation, it is necessary to pay attention to the principles of curriculum development, namely the principles of relevance, effectiveness and efficiency, continuity, flexibility, goal-orientation, as well as the principles of lifelong education. This research uses a library research approach. In this library research, the process of collecting, analyzing, processing and presenting books, journals and texts related to the research theme is carried out as reference material in the form of library reports. Madrasah Aliyah Al Falaahiyyah has started implementing the independent curriculum since last year. Apart from the fact that the ministry requires the implementation of the curriculum, this is an effort for the Madrasah to take a step forward to provide wider space for creativity and innovation in learning. Madrasas strive to present an appropriate curriculum that includes the principles of curriculum development in it. This aims to ensure that the curriculum can be implemented optimally. Overall, the application of these principles ensures that the madrasa curriculum is not only effective in achieving academic and spiritual goals, but also efficient in the use of resources, relevant to the needs of the times, and flexible to support the long-term development of student potential.